Ocean Acidification: Impacts on Marine Ecosystem and Fisheries - Madhulika; Ngasotter, Soibam (Chronicle of Bioresource Management, 2021)
Ocean acidification occurs when environmental carbon dioxide dissolves in seawater, forming carbonic acid, which lowers the pH of the ocean. This phenomenon is majorly driven by human activities like the consumption of fuels and other land-based activities. Ocean acidification has been shown to have an impact on organisms’ homeostasis and ecosystems, posing a risk to fisheries and aquaculture as well as several ecosystem services, coastal protection, and transportation. It is important to have awareness about the potential effects of ocean acidification on the oceanic environment and organisms so that possible prevention and control strategies such as periodical monitoring of carbonate chemistry, management of coastal wastes, limitation of wastes from main point sources and new marine water policies can be developed for the betterment of the marine environment and socioeconomic development of human communities that rely on them.